Mesenchymal Stem Cells Suppress Inflammatory Cytokines in Lipopolysaccharide Exposed Preterm and Term Human Pregnant Myometrial Cells - Mani, Arunmani; Hotra, John; Blackwell, Sean C.; Goetzl, Laura; Refuerzo, Jerrie S. (American Journal of Perinatology Reports, 2024)
Objective The objective of this study was to determine the cytokine response in human pregnant preterm and term myometrial cells exposed to lipopolysaccharide (LPS) and cocultured with mesenchymal stem cells (MSCs).Study Design Myometrium was obtained at cesarean delivery in term and preterm patients. Human myometrial cells were exposed to 5 μg/mL LPS for 4 hours followed by 1 μg/mL LPS for 24 hours and were cocultured with MSCs for 24 hours. Culture supernatants were collected at 24 hours and expression of cytokines, including interleukin-1β (IL-1β), IL-6, IL-8, tumor necrosis factor-α (TNF-α), transforming growth factor-β (TGF-β), and IL-10, was quantified by enzyme-linked immunosorbent assay.Results There was significantly increased expression of the proinflammatory cytokines IL-1β, IL-6, IL-8, and TNF-α in preterm myometrial cells treated with LPS compared with untreated preterm myometrial cells. Coculture with MSCs significantly suppressed the proinflammatory cytokine levels in LPS-treated preterm versus treated term myometrial cells. Moreover, MSC cocultured preterm myometrial cells expressed increased levels of the anti-inflammatory cytokines TGF-β and IL-10 compared with treated term myometrial cells.Conclusion MSCs ameliorate LPS-mediated inflammation in preterm human myometrial cells compared with term myometrial cells. Immunomodulatory effects of MSCs mediated through anti-inflammatory cytokine regulation suggest a potential cell-based therapy for preterm birth.
Keywords: preterm birth; inflammation; cytokines; mesenchymal stem cells; immunomodulation